2009
DOI: 10.1021/jm901044z
|View full text |Cite
|
Sign up to set email alerts
|

N-Sulfonylanthranilic Acid Derivatives as Allosteric Inhibitors of Dengue Viral RNA-Dependent RNA Polymerase

Abstract: A novel class of compounds containing N-sulfonylanthranilic acid was found to specifically inhibit dengue viral polymerase. The structural requirements for inhibition and a preliminary structure-activity relationship are described. A UV cross-linking experiment was used to map the allosteric binding site of the compound on the viral polymerase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 21 publications
0
49
0
Order By: Relevance
“…Chemistry synthesis was performed to study the SAR of the "hit." The details of the SAR results were recently published (45). The SAR study generated NITD-2 which had an improved IC 50 of 0.7 M (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Chemistry synthesis was performed to study the SAR of the "hit." The details of the SAR results were recently published (45). The SAR study generated NITD-2 which had an improved IC 50 of 0.7 M (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Docking and molecular simulation suggest that the compound binds to the RNA template formed between the fingers and thumb subdomains; the detailed methods for modeling was recently reported (45). Two RdRp residues, Arg737 and Thr413, form distinct hydrogen bond interactions with the inhibitor; the observed interactions were maintained during the course of the dynamics simulations, indicating their roles in stabilizing the compound in the allosteric binding pocket (45). Sequence alignment showed that residue Arg737 is conserved among mosquito-borne flavivirus NS5, whereas residue Thr413 is divergent among various members of flavivirus.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Edavorone (197) was introduced in the market by Mitsubishi Pharma in 2001 as a neuroprotective agent (improving neurological recovery following acute brain infarction).…”
Section: 188mentioning
confidence: 99%